Criminal Sanctions Fine For Corporations as Performers of Criminal Acts of Corruption From the Perspective of the Theory of Dignified Justice - Ismaidar Ismaidar; T. Riza Zarzani; Ongku Sapna Fella Hasibuan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Korganization in nation building is very significant. Corporations can be said to be pillars of the nation's economy. Corporations are very influential not only on economic aspects, but also social, political and other aspects. As time goes by, crimes committed by corporations arise. The Criminal Code which does not recognize corporations as legal subjects opens up opportunities for individuals to take advantage of this legal loophole. The regulations governing corporate responsibility currently in effect are considered less effective and efficient. Provisions that clearly regulate